In(tra)fusion: Kitchen research practices, collaborative writing, and re-conceptualising the interview. (February 2018) - Alexander, Dagmar; Wyatt, Jonathan
At the end of our year-long funded collaborative writing project we met to write. We created a writing cocoon around Dagmar's kitchen table (why are kitchens so conducive to work? Is it the smell, the promise of being fed? The clutter? The hiss of the kettle?), and sat with each other, sat with our laptops. We listened to taped voices. We wrote. We wrote in response to what we heard and what we imagined we heard. We listened with each other to others. We read our responses aloud, re-wrote ourselves into each other's responses, and wove filigree threads, some of which held where others broke. These kitchen research practices led us to a response to the ontological, epistemological and methodological difficulties with the qualitative research interview. We offer 'in(tra)fusion' as a re-calibrating, a re-casting, a re-conceptualising, as the familiar becomes strange.